Underlying Skills of Oral and Silent Reading Fluency in Chinese: Perspective of Visual Rapid Processing - Zhao, Jing; Kwok, Rosa K. W.; Liu, Menglian; Liu, Hanlong; Huang, Chen (Frontiers in Psychology, 2017)
Reading fluency is a critical skill to improve the quality of our daily life and working efficiency. The majority of previous studies focused on oral reading fluency rather than silent reading fluency, which is a much more dominant reading mode that is used in middle and high school and for leisure reading. It is still unclear whether the oral and silent reading fluency involved the same underlying skills. To address this issue, the present study examined the relationship between the visual rapid processing and Chinese reading fluency in different modes. Fifty-eight undergraduate students took part in the experiment. The phantom contour paradigm and the visual 1-back task were adopted to measure the visual rapid temporal and simultaneous processing respectively. These two tasks reflected the temporal and spatial dimensions of visual rapid processing separately. We recorded the temporal threshold in the phantom contour task, as well as reaction time and accuracy in the visual 1-back task. Reading fluency was measured in both single-character and sentence levels. Fluent reading of single characters was assessed with a paper-and-pencil lexical decision task, and a sentence verification task was developed to examine reading fluency on a sentence level. The reading fluency test in each level was conducted twice (i.e. oral reading and silent reading). Reading speed and accuracy were recorded. The correlation analysis showed that the temporal threshold in the phantom contour task did not correlate with the scores of the reading fluency tests. Although the reaction time in visual 1-back task correlated with the reading speed of both oral and silent reading fluency, the comparison of the correlation coefficients revealed a closer relationship between the visual rapid simultaneous processing and silent reading. Furthermore, the visual rapid simultaneous processing exhibited a significant contribution to reading fluency in silent mode but not in oral reading mode. These findings suggest that the underlying mechanism between oral and silent reading fluency is different at the beginning of the basic visual coding. The current results also might reveal a potential modulation of the language characteristics of Chinese on the relationship between visual rapid processing and reading fluency.